Sistema de gestão da inovação - ISO 56002: proposta de framework que evidencia o processo de transferência de tecnologia - Barboza, Bertiene Maria Lack (2021)
The systems of standards for the innovation management contribute to increase the awareness of companies and institutions about innovation, favoring the technology transfer as a process that contributes to the development of society. ISO 56002 facilitates the development of structures that improve the technological capacity of developing countries, supporting industrial diversification and adding value. In this context, the aim of this research is to present the proposal for a framework from the implementation of ISO 56002 in favor of technology transfer. To develop this framework, a systematic literature review was carried out considering the themes of innovation, standardized innovation management systems, ISO 56002 and the technology transfer process. The present study shows how the portfolio of articles used for the systematic literature review is elaborated, and how the identification of the ISO 56002 guidelines and the components of the technology transfer process for the development of the characterization framework of the management for transfer of information occurs. technology based on ISO 56002. The results of the work point out the relationship between ISO 56002 guidelines and technology transfer, through three perceived demands. Then he elaborated the proposal for the characterization framework of this process by means of two companies implemented from the system proposed by ISO, where the scenario is contextualized, presenting all the elements, and how it represents the flow and the technology transfer agreement between the two organizations. Finally, the characterized evidenced the relationship between the actors involved, showing that the environment installed by ISO for the management of innovation allows to place the organization in a susceptible scenario to explore partnerships; puts the customer as a central object, and it is evident that the barriers of the process are mitigated in a favorable environment for technology transfer.